Plastics are a new threat to Palau's coral reefs. - Eric Béraud; Vanessa Bednarz; Ikelau Otto; Yimnang Golbuu; Christine Ferrier-Pagès (PLoS ONE, 2022)
Plastic pollution of the oceans has long been an ongoing and growing problem. Single-use plastic (plastic bags and microbeads) is responsible for most of this pollution. In recent years, studies have highlighted the importance of the size of plastic particles, and the impact of this pollution source on the environment. We determined the concentration of small marine plastics in seawater, sediments and beach sand around a pristine reef area (Republic of Palau) using very simple tools (plankton net, sieves, organic matter degradation, density separation, Nile red fluorochrome). In this study, we succeeded in detecting microplastic (MPs) particles and microplastic fibers, but also nanoplastic (NPs). These three types of particles were found in all samples with a large heterogeneity, from 0.01 to 0.09 particles L-1 and 0.17 to 32.13 particles g-1 DW for MPs in seawater, sediments and sand, respectively. Even when NPs were identified, the amounts of NPs were underestimated and varied from 0.09 to 0.43 particles L-1 in seawater and from 1.08 to 71.02 particles g-1 DW in sediment and sand, respectively. These variations could be attributed to the environmental characteristics of the different sites. This study shows that plastic pollution must be considered in environmental studies even in the most pristine locations. It also shows that NPs pollution is related to the amount of MPs found at the sites. To understand the effects of this plastic pollution, it is necessary that the next toxicological studies take into account the effects of this fraction that makes up the NPs.